2016
DOI: 10.1038/srep33470
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Y1 receptor impairs osteoclast bone-resorbing activity

Abstract: Y1 receptor (Y1R)-signalling pathway plays a pivotal role in the regulation of bone metabolism. The lack of Y1R-signalling stimulates bone mass accretion that has been mainly attributed to Y1R disruption from bone-forming cells. Still, the involvement of Y1R-signalling in the control of bone-resorbing cells remained to be explored. Therefore, in this study we assessed the role of Y1R deficiency in osteoclast formation and resorption activity. Here we demonstrate that Y1R germline deletion (Y1R−/−) led to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Conditioned medium from osteoclasts precursors was collected, centrifuged at 140 g, 4°C, 5 min, and stored at −80°C. Adherent cells were then detached with a cell scrapper and seeded at a density of 5 × 10 4 cells/cm 2 in the presence of 30 ng/mL M-CSF and 100 ng/mL receptor activator of nuclear factor kappa-B ligand (RANKL, PeproTech) (Bartell et al, 2014; Sousa et al, 2016). Cells were also seeded on top of bone slices (boneslices.com, Denmark) to collect the secretome from active resorbing osteoclasts.…”
Section: Methodsmentioning
confidence: 99%
“…Conditioned medium from osteoclasts precursors was collected, centrifuged at 140 g, 4°C, 5 min, and stored at −80°C. Adherent cells were then detached with a cell scrapper and seeded at a density of 5 × 10 4 cells/cm 2 in the presence of 30 ng/mL M-CSF and 100 ng/mL receptor activator of nuclear factor kappa-B ligand (RANKL, PeproTech) (Bartell et al, 2014; Sousa et al, 2016). Cells were also seeded on top of bone slices (boneslices.com, Denmark) to collect the secretome from active resorbing osteoclasts.…”
Section: Methodsmentioning
confidence: 99%
“…Genotyping was performed using a PCR-based method to detect WT and knockout alleles. 9,10 On the day before the culling, mice were fasted overnight. In the next morning, mice were anesthetized with a Ketamine (150 mg/Kg) + Medetomidine (2 mg/Kg) solution and blood was collected by cardiac puncture until complete exsanguination.…”
Section: Animals and Tissue Collectionmentioning
confidence: 99%
“…The sympathetic neurons of the peripheral nervous system that project to the bone microenvironment release sympathetic neurotransmitters, such as the Neuropeptide Y (NPY), that activate receptors expressed by bone resident cells. [7][8][9] In this regard, NPY Y 1 receptor (Y 1 R) has been the major NPY signaling pathway shown to play a powerful regulatory action in bone remodeling, 10,11 fracture healing, 12 and bone repair. 13 Important insights from functional and genetic studies revealed that the absence of NPY Y 1 R sympathetic pathway promotes an increase in the bone mass and mineral apposition, which were consistent in femoral, tibial, and vertebral bones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations